A mechanistic study on kinetic compensation effect during low-temperature oxidation of coal chars - Yip, Kong; Ng, Esther; Li, Chun-Zhu; Hayashi, J.; Wu, Hongwei (Elsevier, 2011)
This paper provides mechanistic insights into the low-temperature oxidation of a range of carbon materials (graphite, a sub-bituminous coal char, and a brown coal char). Kinetic analysis was carried out on oxidation of the chars, prepared from fast-heating pyrolysis, under chemical-reaction-controlled regime. FT-Raman spectroscopic analysis was adopted to provide direct structural information on the carbon structure of reacting carbon materials throughout oxidation. The results demonstrate the significance of selective oxidation under the conditions, and parallel to this, the kinetic compensation effect of carbon oxidation reaction throughout conversion for all samples. Supported by the results from FT-Raman spectroscopy, the kinetic compensation effect seems to be a result of the selective oxidation of these carbon materials with heterogeneous carbon structures. Oxidation of all samples, with or without catalysts, appears to be similar in terms of the ‘nature’ of carbon structural condensation during low-temperature oxidation, suggesting a similar increase in apparent active sites population with respect to increase of apparent energy barrier. Under the current experimental conditions, a general kinetic compensation effect correlation has been deduced for various materials, requiring only the initial char kinetic parameters. The inherent inorganic species in chars also seem to alter the ‘degree/extent’ of carbon structural condensation as results of selective oxidation. In this case, the use of the compensation effect correlation will require more information on the catalysis during oxidation, apart from the initial char kinetic parameters.